It happened in the White House : extraordinary tales from America's most famous home - Karr, Kathleen; Meisel, Paul. (New York : Hyperion Books for Children, 2001)
True stories and facts about the White House.
Includes bibliographical references (p. 106-108) and index.
G6
Keywords: White House (Washington, D.C.) -- Miscellanea -- Juvenile literature; Presidents -- United States -- Miscellanea -- Juvenile literature; Washington (D.C.) -- Buildings, structures, etc. -- Miscellanea -- Juvenile literature